Synthesis and Structural Characterization of Some Lanthanide(III) Nitrate Complexes with a Mesogenic Schiff-Base, N,N’-di-4-(4’-heptadecyloxybenzoate) salicylidene-1,3-diaminopropane Derived from 2,4- dihydroxybenzaldehyde - Shrestha, Prem Kumar; Shakya, Pawan Raj (Journal of Nepal Chemical Society, 2020)
Complexes of La(III), Pr(III), Nd(III), Sm(III), Gd(III) and Dy(III) with the Schiff-base, N,N′-di-4-(4’-heptadecyloxybenzoate)salicylidene-1,3-diaminopropane, (abbreviated as H2L) have been synthesized and characterized on the basis of elemental analyses, molar conductance, magnetic, electronic, infrared, 1H and 13C NMR spectral techniques. The nephelauxetic ratio (β), the bonding parameter (b1/2), Sinha’s parameter (%δ) and angular overlap parameter (η) have been calculated from the electronic spectra of Pr(III), Nd(III), Sm(III) and Dy(III) complexes. Infrared and NMR spectral data imply a bi-dentate bonding of the Schiff-base in its zwitterionic form (as LH2) to the Ln(III) ions through two phenolate oxygens, rendering the overall geometry around Ln(III) to distorted square antiprism. Polarized optical microscopy (POM) and differential scanning calorimetry (DSC) shows the liquid crystalline property of the ligand with a nematic (N) mesophase. Among the metal complexes, only that of the Gd(III) exhibits smectic B (SmB) and nematic (N) phases.